URGENSI ASAS LEGALITAS DALAM PEMBAHARUAN HUKUM PIDANA NASIONAL DI INDONESIA - Yasanegara, I Gde (Kerta Dyatmika, 2016)
ABSTRACTÂ The design of the draft Kitab Undang-Undang Hukum Pidana (RUU KUHP), a "Design Build" the National Criminal Justice System which intends to "build / update / create a new system". Build or reform law ( "law reform", particularly the "penal reform") is essentially a "build or renew the points thinking / concept / idea-essentially," not just to update / change the formulation of the articles textually.Preparation of the New KUHP concept is motivated by the needs and demands of national reforms, and once the change / replacement of the old KUHP (Wetboek van Strafrecht) legacy of the Dutch colonial era. When referring to the RUU KUHP in Indonesia seem legality principle does not apply in absolute terms. This can be seen in chapter 1, article 2 and article 3 of the Indonesian RUU KUHP.Â  In the context of the size of the enactment of national criminal law principle of legality include the lex scripta and lex certa or by any written law and clear rules that are not justified the enactment of the principle of legality only by the common law. Likewise, in the context of national criminal law criminal provisions must be interpreted strictly as a manifestation principle of lex stricta.Â